Howards End: O Espaço nas Narrativas Literária e Fílmica - Souza, José Ailson Lemos de (2012)
This dissertation examines the construction of space in two narratives: the novel Howards End (1910), by E. M. Forster, and the homonymous film (1992), directed by James Ivory. Our hypothesis is that the film makes use of spatial elements to comment on the film genre itself: the heritage films; and so, it reformulates the initial discourse with which such narratives were related to. Thereby, the function of space in the film is different from that function used in the novel. It is, therefore, a translation strategy which places Ivory’s text in a dialectical relation with its own time, although it tries to recreate Edwardian period on screen. In order to demonstrate our interpretation, we firstly examined the space in the novel. We concluded that, in this text, the space has the following functions: to symbolically discuss the complexity of male and female genres, showing the arbitrary way by which this question was seen at the beginning of the 20th century, and the representation of the house as a place of refuge from the feeling of fragmentation in society; exterior places function as sceneries in which the deep changes brought by modernity are reflected. In the film, however, space is used to construct the aesthetics of display, a typical characteristic of heritage films, to modify the notions on English identity commonly related to these narratives. If, at the beginning, heritage films discourse attempted to redeem British imperialistic position, Ivory’s film deconstructs such attempt and indicates its impossibility. Our work is based on concepts from Descriptive Translation Studies, from polysystem theory by Even-Zohar (1990), Lefevere’s concept of rewriting, and on studies that deal with film narratives such as Vanoye & Goliot-Lété (1994), Aumont (1995), Silva (2007) and Gaudreault & Jost (2009)